Nālah-i ʿāṣim : ẕaẖīrah-i barakat-i maʿdan-i saʿādat bayān-i vilādat-i šāfiʿ-i umam-i Muḥammad Muṣt̤afā (Naval Kišor, 1887)
A short devotional-hagiographical account of the birth of the Prophet Muhammad with much embedded poetry, mostly the author's elaboration on popular odes (naʻt and manqabat)